2016
DOI: 10.1007/s00449-016-1536-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen transfer on Pseudomonas putida effects on growth rate and biodesulfurization capacity

Abstract: The growth rate and desulfurization capacity accumulated by the cells during the growth of Pseudomonas putida KTH2 under different oxygen transfer conditions in a stirred and sparged tank bioreactor have been studied. Hydrodynamic conditions were changed using different agitation conditions. During the culture, several magnitudes associated to growth, such as the specific growth rate, the dissolved oxygen concentration and the carbon source consumption have been measured. Experimental results indicate that cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 31 publications
5
31
0
Order By: Relevance
“…Microbial growth rate has been described according to Equation (3), employed in previous work for different bioprocesses: dCXdt=μmaxCX()1CXCXitalicmax If this equation is integrated with the boundary condition ( t = 0 ; C X = C X 0 ), the logistic growth equation is obtained: CX()t=CX0exp()μmaxt1CX0CXitalicmax[]1exp()μmaxt …”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbial growth rate has been described according to Equation (3), employed in previous work for different bioprocesses: dCXdt=μmaxCX()1CXCXitalicmax If this equation is integrated with the boundary condition ( t = 0 ; C X = C X 0 ), the logistic growth equation is obtained: CX()t=CX0exp()μmaxt1CX0CXitalicmax[]1exp()μmaxt …”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…The oxygen mass balance in the liquid phase, assuming well‐mixed culture, can be established by: dCO2dt=OTRitalicOUR OTR depends on the mass coefficient transfer, k L , the specific interfacial area, a , and the driving force of the oxygen transfer, which is the difference between the equilibrium dissolved oxygen concentration in the liquid phase at working pressure and temperature, CO2*, and the DO concentration in the broth, CO2, according to: OTR=kLa·()CO2*CO2 OTR can be determined by an oxygen mass balance in the gas phase by the difference between the inlet and outlet oxygen molar flow rates ( F O2 IN and F O2 OUT , respectively), as follows: FO2INFO2OUTV=OTR Once OTR is determined and DO concentration is measured in the liquid phase, k L a can be calculated directly from Equations (6) and (7), yielding: kLa=FO2INFO2OUTV·()CO2*CO2 Then OUR can be calculated according to Equation (5), once OTR and DO oxygen profile are known, calculating dC O2 /dt by numerical methods, such as those described elsewhere …”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, the optimal cell age was established and the enhancing of the process by addition of co‐substrates was evaluated . Subsequently, a kinetic model was proposed in order to describe the experimental results and the influence of OTR over the biomass growth and the desulfurization capacity was studied, by changing the agitation or the airflow rate …”
Section: Introductionmentioning
confidence: 99%
“…The results showed that, if the culture is carried out at a high agitation, which induces high dissolved oxygen concentration, the growth rate increases and the cells are not affected by shear stress. However, the desulfurization capacity operating with resting cells present a dramatic decrease when the cells are exposed to a stirrer speed higher than 300 rpm …”
Section: Introductionmentioning
confidence: 99%